The Influence of Brand Identification and Brand Trust on Brand Evangelism - Muhammad Fa'iq Muna; Yuslinda Dwi Handini; Wheny Khristianto (Citakonsultindo, 2023)
This study aims to test and determine the effect of brand identification and brand trust on brand evangelism. This study used primary data from questionnaire results. The object of this research is consumers who have made purchases and transactions directly through the Shopee e-commerce application. The method used in this study is a type of explanatory research with a quantitative approach. The sampling technique uses the non-probability sampling method. The survey data was collected online and the sample number of the study was 100 respondents. Data analysis uses multiple linear regression analysis using SPSS as its analysis tool. The results showed that brand identification has a positive and significant effect on brand evangelism. Brand trust has a positive and significant effect on brand evangelism. Brand trust and brand identification have a simultaneous positive and significant effect on brand evangelism. The majority are more dominant in brand trust in brand evangelism than in brand identification. The theoretical implications in this study can contribute to future studies related to the field of brand marketing, especially on brand evangelism which is still not widely studied in Indonesia.